Critical intellectuals, Europe and the small nations - Nieminen, Hannu (Javnost (Ljubljana), 2014)
The quest for more openness and publicity is seen as a continuation of the long historical development of the epistemic commons, which began in the Middle Ages and culminated in the legacy of the Enlightenment. The argument is that European modernity is fundamentally based on the assumption that knowledge and culture belong to the common domain and that the process of democratisation necessarily means removing restrictions on the epistemic commons. Over the last 30 years, this optimism has suffered from two kinds of backlashes. Firstly, from the 1970s onwards, a policy of weakening and privatising public institutions has practically halted the expansion of the epistemic commons. Secondly, the other half of Europe, the CEE countries, did not benefit from the same kind of democratic development after the Second World War as their Western counterparts did. Because there was no tradition of democratic public institutions, the critical intellectuals in the CEE countries were rather helpless in promoting the ideas of publicity and democratic citizenship. The difficult questions are as follows: What can the role of critical scholars in promoting the epistemic commons be today? How should we understand the legacy of the Enlightenment - without falling for nostalgia for the 1960s and 1970s?
Keywords: Europe; Evropa; democracy; demokracija; javnost; intelektualci; human rights; človekove pravice; intelektualna svoboda; kritično mišljenje